The association of maternal vaginal bleeding and progesterone supplementation in early pregnancy with offspring outcomes: a prospective cohort study - Chunrong Zhong; Guoping Xiong; Lixia Lin; Qian Li; Xi Chen; Xu Zhang; Yu Zhang; Shangzhi Xu; Xiaoyi Wang; Duan Gao; Meng Wu; Sen Yang; et al. (BMC, 2022)
Abstract Background Progesterone is widely used to improve the adverse pregnancy outcomes related to vaginal bleeding during early pregnancy. However, the evidence of its effectiveness is equivocal. Methods Six thousand six hundred fifteen mother-infant pairs from Tongji Maternal and Child Health Cohort (TMCHC) were involved in the study. Information on vaginal bleeding, progesterone administration in early pregnancy were obtained at enrolment. Birth outcomes were obtained from the hospital notes. Body weight of the infants at 12 months of age was collected by telephone interview. Multivariable logistic regression was conducted to estimate the effect of vaginal bleeding and progesterone administration in early pregnancy on birth outcomes and weight status of infants at 12 months of age. Results 21.4% (1418/6615) participants experienced bleeding in early pregnancy, and 47.5% (674/1418) of them were treated with progesterone. There were no significant associations between progesterone supplementation in early pregnancy and offspring outcomes. Compared to women without bleeding or any therapy, women with bleeding and progesterone therapy experienced increased risk of preterm (OR 1.74, 95% CI 1.21-2.52), and delivering a small-for-gestational-age (SGA) (OR 1.46, 95% CI 1.07-1.98) or low birth weight (LBW) (OR 2.10, 95% CI 1.25-3.51) neonate, and offspring of them had an increased risk of weight for age z-score (WAZ) < -1 at 12 months of age (OR 1.79, 95%CI 1.01-3.19). Conclusions Offspring of mothers with bleeding and progesterone therapy were more likely to be a premature, SGA or LBW neonate, and had lower weight at 12 months of age. Progesterone supplementation may have no beneficial effect on improving adverse offspring outcomes related to early vaginal bleeding. Trial registration TMCHC was registered at clinicaltrials.gov as NCT03099837 on 4 April 2017.